An MILP model for the plug-in electric vehicle charging coordination problem in electrical distribution systems - Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Romero, Ruben [UNESP] (Ieee, 2014)
A new mixed-integer linear programming (MILP) model is proposed to represent the plug-in electric vehicles (PEVs) charging coordination problem in electrical distribution systems. The proposed model defines the optimal charging schedule for each division of the considered period of time that minimizes the total energy costs. Moreover, priority charging criteria is taken into account. The steady-state operation of the electrical distribution system, as well as the PEV batteries charging is mathematically represented; furthermore, constraints related to limits of voltage, current and power generation are included. The proposed mathematical model was applied in an electrical distribution system used in the specialized literature and the results show that the model can be used in the solution of the PEVs charging problem.
Keywords: Electrical distribution system; Plug-in electric vehicles; Mixed integer linear programming; Optimal charging